(untitled) (Canadian Medical Education Journal, 2024)
Background: International medical graduates (IMGs) are an essential part of the Canadian physician workforce. Considering current pressures on the health care system, an update regarding application numbers and match rates for IMGs to postgraduate positions in Canada is needed. Methods: We conducted a quantitative cross-sectional study to explore the characteristics of IMGs who are currently applying to the Canadian Residency Matching Service (CaRMS) positions to gain a broad understanding of the composition of this group and the factors associated with successful matching. Results: Out of 1,725 applicants in 2019, 14.1% matched on the first attempt and 6.4% after two to three attempts. Only 22.7% matched with a position (57.6% women). Applicants submitted an average 19.6 site/program applications. The percentage of IMGs matched did not statistically differ by gender. The relationship between the year of graduation or geographic area of medical school qualified and matching was significant for the first and second iterations, with current-year graduates and Oceania/Pacific Islands applicants more likely to match. Conclusions: This study provided us with accurate numbers and information about the Canadians studying abroad and IMG groups applying, and factors associated with being matched to the IMG positions through CaRMS, which will be instrumental in informing future selection implications for Canada.